Nevroendoskopija pri bolnikih z intraventrikelnim možganskim tumorjem - Koršič, Marjan (Endoskopska revija, 2007)
The objective of this study was to demonstrate the efficacy and limitations ofendoscopic treatment used in two patients with intraventricular tumors: one without ventricular enlargement and another with hydrocephalus. In the latter a successful endoscopic third ventriculostomy was done. Pathological diagnosiswas made in the first patient only. A neuroendoscopic approach has proved a useful technique for the treatment of selected intraventricular tumors.
Keywords: možgani; neoplasm; tumor; kirurško zdravljenje; endoskopska kirurgija